Education and teenage childbirth in Uganda: Understanding the links from the Uganda Demographic and Health Survey - Makate, Marshall; Makate, C. (Emerald Group Publishing, 2018)
Purpose: The role of increased schooling on teenage childbirth has been expansively studied especially in developed countries. However, caveats remain in the case of low-income countries especially Sub-Saharan Africa. The purpose of this paper is to ascertain the impact of increased schooling on the probability of first childbirth at 15 years or younger, 16-17, 18-19, and 20 years or older, in the important context of Uganda – a country with one of the highest adolescent fertility rates in Africa. Design/methodology/approach: The empirical analysis uses recent data from the nationally representative Demographic and Health Survey for Uganda conducted in 2011. The authors then adopt a fuzzy regression discontinuity design, estimated using instrumental variables techniques that exploit the exogenous change in schooling impelled by the universal primary education policy enacted in 1997 in Uganda. The empirical approach compares the fertility outcomes for women born in 1984-1992 (i.e. exposed to the policy) to those born in 1973-1981 (i.e. non-exposed). Findings: The authors find that a one-year increase in schooling lowers the probability of first childbirth at age the age of 15 years or younger, 16-17, 18-19, and 20 years or older by nearly 8.2, 9.2, 9.4, and 9.5 percentage points, respectively. Also, pathways through which education impacts teenage motherhood included information access through the media, increased literacy, prenatal care utilization, marital status, and unhealthy sexual behavior. Originality/value: The paper uses nationally representative survey data to scrutinize the causal influence of schooling on the probability of first childbirth using the 1997 universal primary education in Uganda as a natural experiment to identify the impact of schooling. The study recommends that expanding primary schooling opportunities for girls may be an effective strategy toward accelerated reductions in teenage fertility in Uganda.